The Oxford handbook of interdisciplinarity - Frodeman, Robert; Klein, Julie Thompson; Pacheco, Roberto C. S. (Oxford, United Kingdom : Oxford University Press, 2017)
This title provides a synoptic overview of the current state of interdisciplinary research, education, administration and management, and problem solving - knowledge that spans the disciplines and interdisciplinary fields and crosses the space between the academic community and society at large.
The future of interdisciplinarity : an introduction to the 2nd edition / Robert Frodeman -- Sidebar : mathematics and root interdisciplinarity : historical perspectives / Erik Fisher, David Beltran-del-Rio -- Integrating the social sciences : area studies, quantitative methods, and problem-oriented research / Craig Calhoun -- Interdisciplinary arts / Tanya Augsburg -- Interdisciplining humanities : a historical overview / Julie Thompson Klein, Robert Frodeman -- Digital humanities : the role of interdisciplinary humanities in the information age / Cathy N. Davidson, Danica Savonick -- A field of its own : the emergence of science and technology studies / Sheila Jasanoff -- Cognitive science / Paul Thagard -- Media and communication / Adam Briggle, Clifford G. Christians -- Situating feminist studies / Ellen Messer-Davidow -- Humane smart cities / Eduardo M. Costa, {u206C}varo D. Oliveira -- Knowledge formations : an analytic framework / Stephen Turner -- Interdisciplinarity in ethics / Carl Mitcham, Nan Wang -- Sidebar : an ethics of interdisciplinary research / Anne Balsamo -- Interdisciplinary learning : a cognitive-epistemological foundation / Veronica Boix Mansilla -- Comparing methods for cross-disciplinary research / Michael O'Rourke -- Systems thinking / Sytse Strijbos -- Innovation, interdisciplinarity, and creative destruction / Roberto C.S. Pacheco, Mauricio Manh{u4865}s, Mauricio Uriona Maldonado -- Addressing wicked problems through transdisciplinary research / Christian Pohl, Bernhard Truffer, Gertrude Hirsch-Hadorn -- Sidebar : managing consensus in inter- and transdisciplinary teams : tasks and expertise / Rico Defila, Antonietta di Giulio -- Understanding cross-disciplinary team-based research : concepts and conceptual models from the science of team science / Kara Hall, Brooke A. Stipelman, Amanda L. Vogel, Daniel Stokols -- The policy sciences as a transdisciplinary approach for policy studies / Jason Vogel, David N. Cherney, Elizabeth A. Lowham -- Typologies of interdisciplinarity : the boundary work of definition / Julie Thompson Klein -- Sustainability sciences : political and epistemological approaches / Valdir Fernandes, Arlindo Philippi Jr. -- Religious studies and religious practice / Sarah E. Fredericks -- Interdisciplinarity in the fields of law, justice, and criminology / Stuart Henry -- Health research, practice, and education / Angus McMurtry, Kelly N. Kilgour, Shanta Rohse -- Sidebar : new public service through coproduction / JosFrancisco Salm Jr., Roberto C.S. Pacheco -- Information research / Carole L. Palmer, Katrina Fenlon -- Computation and simulation / Johannes Lenhard -- Taming wickedness by interdisciplinary design / Prasad Boradkar -- Interdisciplinarity and the institutional context of knowledge in the American research university / Michael M. Crow, William B. Dabars -- Peer review, interdisciplinarity, and serendipity / J. Britt Holbrook -- Sidebar : the need for disciplines in the modern research university / Jerry A. Jacobs -- Interdisciplinarity in research evaluation / Katri Huutoniemi, Ismael Rafols -- The challenge of funding interdisciplinary research : a look inside public research funding agencies / Thomas Kig, Michael E. Gorman -- Sidebar : toward a new discipline of integration and implementation sciences / Gabriele Bammer -- Administering interdisciplinary programs / Karri Holley -- Interdisciplinarity and the student voice / Carl Gombrich, Michael Hogan -- Interdisciplinary pedagogies in higher education / Debora DeZure -- Doctoral student and early career academic perspectives on interdisciplinarity / Sarah Dooling, Jessica K. Graybill, Vivek Shandas -- Facilitating interdisciplinary scholars / Stephanie Pfirman, Paula J.S. Martin -- Interdisciplinary cases and disciplinary knowledge: epistemic challenges of interdisciplinary research / Wolfgang Krohn -- The military-industrial route to interdisciplinarity / Steve Fuller -- Physical sciences / Robert P. Crease -- Interdisciplinarity and the earth sciences : transcending limitations of the knowledge paradigm / Victor R. Baker -- Interdisciplinarity in the biological sciences / Warren Burggren, Kent Chapman, Bradley B. Keller, Michael Monticino, John S. Torday.
Series title from dust jacket.
Includes bibliographical references and index.
Keywords: Interdisciplinary approach to knowledge; Interdisciplinary research; Cognitive science -- Research